Eugenol-derived reconfigurable high-performance epoxy resin for self-deployable smart 3D structures - Miao, Jia-Tao; Ge, Meiying; Wu, Yadong; Chou, Tsung Yu; Wang, Haopeng; Zheng, Longhui; Wu, Lixin (European polymer journal, 2020)
[Display omitted] •Eugenol-derived epoxy resin (TMOPP/DTDA) with dynamic disulfide bonds was fabricated.•TMOPP/DTDA resin had superior thermal, mechanical properties and flame retardancy.•The permanent shape reconfigurability of TMOPP/DTDA resin was achieved.•Self-deployable ability of TMOPP/DTDA resin was obtained.•A planar film could self-deploy to a 3D “rocking chair” structure. Fabricating biobased reconfigurable high performance epoxy resins for self-deployable 3D smart structures is an interesting issue with great challenge. Herein, a biobased trifunctional epoxy monomer (tris(2-methoxy-4-(oxiran-2-ylmethyl)phenyl) phosphate, TMOPP) was derived from eugenol and cured by 4,4′-dithiodianiline (DTDA) to form the dynamic cross-linked TMOPP/DTDA resin. The integrated properties including thermal, mechanical and flame retardancy of TMOPP/DTDA resin are studied systemically. Compared with commercial epoxy resin (diglycidyl ether of bisphenol A (DGEBA)/DTDA), TMOPP/DTDA resin has higher glass transition temperature (217 °C) and tensile strength (95.2 MPa), while these properties are superior to those of biobased dynamic cross-linked epoxy resins reported in literatures. TMOPP/DTDA resin also shows excellent flame retardancy with UL-94 V-0 rating. The trifunctional aromatic structure of TMOPP and the compact cross-linked structure of TMOPP/DTDA resin play a principle role in the outstanding performances. At the same time, permanent shape reconfigurability and self-deployable ability of TMOPP/DTDA resin was exhibited by the transformation from planar film into a 3D “rocking chair” structure. These results provide a new method to produce biobased reconfigurable high performance epoxy resin in a simple and sustainable way, while expand the application of dynamic cross-linked epoxy resins in self-deployable 3D smart structures.